Female governance and performance - Bianchi, Maria Teresa; Morrone, Carla; Ricco, Sabrina; Faioli, Donato (Piccola Impresa / Small Business, 2021)
The purpose of this research is to investigate the correlation between female presence in the governance and corporate performance. To make the survey meaningful, the sample is composed of small and medium-sized enterprises that are more representative of Italian entrepreneurship than the listed or, in any case, larger companies. The construction of the sample is based on a big data model, which has allowed to consider a significant number of variables in order to determine companies’ performance and the related health status. The correlation between performance and female presence in the governance is not highlighted, showing that the choice of directors should be based on individual's skills and competences regardless of gender.